2001
DOI: 10.1023/a:1010748316889
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Five experimental models were developed in different groups of Wistar rats (N = 15) to study selective COX-2-inhibitor NSAIDs such as celecoxib and rofecoxib, as follows: (1) dose-dependent oral Celecoxib and Rofecoxib for 5 days, and 24 hr after oral indomethacin; (2) Same as 1 but subcutaneously; (3) gastric ulcer induced by glacial acetic acid; (4) duodenal ulcer induced by cysteamine; and (5) stress by immobilization and immersion in water at 15 degrees C for 6 hr. Celecoxib and Rofecoxib, either orally or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…given to four animals to obtain the corresponding doseresponse. The doses were chosen in the therapeutic range from preliminary pharmacokinetic data, eicosanoid profiles, and current literature (20)(21)(22)(23). For instance, celecoxib was administered at higher doses because it has a larger volume of distribution and is less efficacious when compared with rofecoxib.…”
Section: Methodsmentioning
confidence: 99%
“…given to four animals to obtain the corresponding doseresponse. The doses were chosen in the therapeutic range from preliminary pharmacokinetic data, eicosanoid profiles, and current literature (20)(21)(22)(23). For instance, celecoxib was administered at higher doses because it has a larger volume of distribution and is less efficacious when compared with rofecoxib.…”
Section: Methodsmentioning
confidence: 99%
“…Slomiany's group 54) found that platelet-activating factor (PAF) inhibitor, BN52020, significantly delayed the healing of acetic acid ulcers in rats, possibly due to decreased COX-2 protein expression, an increased rate of epithelial cell apoptosis, and increases in TNFa and mucosal NOS-2 activity. Laudanno et al 55) reported that both celecoxib and rofecoxib significantly aggravated and complicated gastric ulcers induced by acetic acid methods.…”
Section: Cox-2 and Paf Inhibitors And Plateletsmentioning
confidence: 99%
“…[56] Third, discontinuation of MTX and LEF combination therapy and the use of symptomatic treatment resulted in marked improvement of our patient's condition, suggesting that a drug-related adverse reaction had occurred. Fourth, although other concomitant agents, such as celecoxib, can cause gastrointestinal damage and increase bleeding risk,[9] hematologic toxicity associated with celecoxib has not been reported thus far. However, methylprednisolone can stimulate the hematopoietic function of bone marrow, increasing the number of circulating neutrophils and platelets as well as inducing erythropoiesis; moreover, as the actions of several other agents included in adjuvant therapy are mild without side effects of this type, the contribution of other concomitant agents can be excluded.…”
Section: Discussionmentioning
confidence: 99%